2017
DOI: 10.1111/jora.12325
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Year Emotional Intelligence Intervention to Reduce Adolescent Aggression: The Mediating Role of Unpleasant Affectivity

Abstract: Adolescents' aggressive behavior is a growing social problem with important implications for psychosocial adjustment. The teaching of emotional skills has an important impact on reducing aggression in schools. However, little scientific evidence has shown the explanatory mechanism through which this training reduces aggression during adolescence. This article aims to provide evidence for the effectiveness of a 3-year longitudinal intervention among adolescents in nine Spanish schools. A total of 476 adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
0
28
0
5
Order By: Relevance
“…In addition, these programs have shown positive results on psychological adjustment ( Sklad et al, 2012 ), coexistence and a supportive environment in the classroom ( Rivers et al, 2013 ), self-esteem and self-control ( Coelho et al, 2016 ), and student well-being ( Taylor et al, 2017 ). In addition, some interventions have effectively prevented emotional symptoms such as depression and anxiety ( Durlak et al, 2011 ), conflict in the classroom ( Machado Azeredo et al, 2015 ), sexual harassment perpetration ( Espelage et al, 2015 ), and aggressive behavior ( Castillo-Gualda et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these programs have shown positive results on psychological adjustment ( Sklad et al, 2012 ), coexistence and a supportive environment in the classroom ( Rivers et al, 2013 ), self-esteem and self-control ( Coelho et al, 2016 ), and student well-being ( Taylor et al, 2017 ). In addition, some interventions have effectively prevented emotional symptoms such as depression and anxiety ( Durlak et al, 2011 ), conflict in the classroom ( Machado Azeredo et al, 2015 ), sexual harassment perpetration ( Espelage et al, 2015 ), and aggressive behavior ( Castillo-Gualda et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interventions were mainly delivered by teachers and psychologists who participated in training sessions, prior to program implementation (Brackett, Rivers, Reyes, & Salovey, 2012;Dougherty & Sharkey, 2017;. In the analyzed studies, both short-term programs (Di Fabio & Kenny, 2011) as well as long-term programs were identified (Castillo-Gualda, Cabello, Herrero, Rodríguez-Carvajal, & Fernández-Berrocal, 2018).…”
Section: Program Delivery Characteristicsmentioning
confidence: 99%
“…The interventions sessions were delivered weekly and the approximate duration of a session was one hour (Castillo-Gualda, Cabello, Herrero, Rodríguez-Carvajal, & Fernández-Berrocal, 2018;Coelho, Marchante, & Sousa, 2015).…”
Section: Program Delivery Characteristicsmentioning
confidence: 99%
“…In the review of the literature, it is confirmed that the connexion between the aggression modalities and some variables such as the emotional intelligence, the values, and the family functioning, if the rapport among them is negative [34], social and personal values are reduced [35], and there is a higher risk of family dysfunction [36].…”
Section: Variables Related To Aggressive Behaviormentioning
confidence: 99%
“…However, within the group of victims there were no significant differences. The correlation between the modalities of aggression and the variables of emotional intelligence, values and family function showed a negative relation since the higher levels of aggressiveness, the lower levels of emotional intelligence [28,34], personal and social values are also reduced and there is a higher risk of family disfunction [33,36].…”
mentioning
confidence: 99%